2018
DOI: 10.2169/internalmedicine.0312-17
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Carbapenem Non-susceptible <i>Campylobacter coli</i> after Long-term Treatment against Recurrent Bacteremia in a Patient with X-linked Agammaglobulinemia

Abstract: We herein report a case of recurrent Campylobacter coli bacteremia in a 37-year-old Japanese man with X-linked agammaglobulinemia (XLA). The patient experienced seven episodes of C. coli bacteremia over one year, with an erythematous rash intermittently emerged on the lower limbs. Although hospitalization for intravenous treatment was repeatedly recommended, he obstinately declined it. Following long-term oral antibiotic treatment with tebipenem and faropenem for the persistent infection, C. coli showed elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Carbapenem-non-susceptible Campylobacter strains have already been reported (Hagiya et al, 2018). In Japan, C. coli isolates obtained successively from a patient after long-term treatment against recurrent bacteremia had an elevated MIC for meropenem (1 mg/L, then 4 mg/L).…”
Section: Overall Proposalmentioning
confidence: 97%
“…Carbapenem-non-susceptible Campylobacter strains have already been reported (Hagiya et al, 2018). In Japan, C. coli isolates obtained successively from a patient after long-term treatment against recurrent bacteremia had an elevated MIC for meropenem (1 mg/L, then 4 mg/L).…”
Section: Overall Proposalmentioning
confidence: 97%
“…Over the past 30 years, carbapenems have played a crucial role in clinical weaponry to treat serious infections in patients primarily affected by multidrug-resistant bacteria. However, the usefulness of this class of antibiotics is being c o m p r o m i s e d b y t h e e m e r g e n c e o f r e s i s t a n c e i n Enterobacteriaceae and especially in Campylobacteriaceae, being considered as a "nightmare" (Perez et al, 2016;Hagiya et al, 2018). In our study, two of these three strains have erythromycin as a treatment option, but one of them, in addition to resistance to meropenem, was also resistant to all other classes of tested antimicrobials.…”
Section: Antimicrobial Resistance Profile In the Planktonic Formmentioning
confidence: 99%
“…For severe infections caused by carbapenemase-producing Enterobacteriaceae, the possibility of treatment is the use of colistin, either singly or in combination with other antibiotics, which does not fit Campylobacter due to its intrinsic resistance (Halaby et al, 2013). Although resistance to carbapenemics in Campylobacter has not yet been well defined by the authorities, a study by Hagiya et al (2018) suggested the existence of resistance due to subsequent exposure to the drug in a clinical situation. Our study demonstrates the first record of phenotypic resistance to meropenem in C. jejuni in Brazil.…”
Section: Antimicrobial Resistance Profile In the Planktonic Formmentioning
confidence: 99%
“…Lastly, there is a case report of Campylobacter coli repeatedly treated with TBP‐PI and faropenem in an adult patient who subsequently developed resistance to TBP‐PI 62 . However, this is also likely due to the underdosing of TBP‐PI in an adult patient as there was no adult dosing guidance available to the clinicians who utilized 200 mg by mouth twice daily (BID).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%